Author guidelines - Standards for submission - Revista Brasileira de Medicina de Família e Comunidade RBMFC (Sociedade Brasileira de Medicina de Família e Comunidade, 2012)
Purpose and Editorial Policy The peer review process Sections and Types of Articles Presentation and Preparation of Manuscripts Electronic Submissions Statement of authorship Sample Statement of Authorship and Responsibility Research ethics Acknowledgments Additional doubts and clarification